The recovery of copper from a pregnant sulphuric acid bioleach solution with developmental resin Dow XUS43605 - Liebenberg, C; Dorfling, C; Bradshaw, S; Akdogan, G.; Eksteen, Jacques (Southern African Institute of Mining and Metallurgy, 2013)
This paper focuses on the application of ion exchange technology for the recovery of copper from a leach solution originating from a heap bioleach in which base metals are leached from a low-grade ore that bears platinum group metals. Screening tests indicated that Dow XUS43605 has high selectivity for copper over the other metals in the solution, namely nickel, iron, cobalt, zinc, manganese, and aluminium. Batch adsorption kinetic experiments showed that copper adsorption equilibrium is attained at a fast rate. The kinetics of adsorption increased as the temperature was increased from 25°Cto 60°C due to the decrease in solution viscosity and the subsequent improved intra-particle mass diffusion. Single-component Langmuir and Freundlich isotherm models were fitted to the batch copper adsorption equilibrium data, and a maximum copper capacity of26 g/l was observed for Dow XUS43605. The effects of flow rate, temperature, pH, and initial metal concentration on the dynamic recovery of copper were investigated in fixed-bed columns, and it was determined that temperature and flow rate had the most significant impacts on the loading of copper on the resin at copper breakthrough. A 36% increase in copper loading at breakthrough was observed when the temperature was increased from 25°C to 60°C. Finally, it was determined that a split elution is possible by using different concentrations of H2SO4 to first elute co-loaded nickel from the resin, followed by the elution of copper.